Sister Boniface mysteries. Season 3 [videorecording (DVD)] - Tindall, Jude (BBC Studios, 2024)
The crime-solving Vespa-driving Catholic nun is back to solve more crimes in this acclaimed murder-mystery series. Sister Boniface's faith in The Almighty is matched only by her passion for forensics. Her aptitude for detective work is an invaluable asset to the Great Slaughter Police Department, who face more mysteries. The head perfumer of a famous fragrance dynasty is found dead, a renowned organist is murdered mid-tune, and a cult sci-fi convention turns ugly when one of the guests is kidnapped. Includes the 2023 Christmas special.